Determinan Praktik Manajemen Laba Pada Perusahaan Bumn Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Ivanda Rizqy Wahyu Brillian; Prima Wulandari, Putu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the existence of earnings management practices assessed by the cash holding, profitability, financial leverage, and firm size of state-owned companies listed on the Indonesia Stock Exchange with managerial ownership as the moderating variable. The samples include 13 state-owned companies listed on the Indonesia Stock Exchange between 2016 and 2020 comprising 65 units of observed data. This study employs descriptive statistics, normality tests, absolute difference tests, determinant coefficient tests, and hypothesis testing (t-test and f-test) to achieve the study objectives. The test results revealed that partially cash holding had a significant positive effect on earnings management, and financial leverage had a significant negative effect on earnings management, while profitability and firm size had no significant effect on earnings management. Managerial ownership moderated the effect of profitability on earnings management, however, was unable to moderate the effect of cash holding, financial leverage, and firm size with earnings management.